Integrasi Nilai-Nilai Pendidikan Islam Moderat Dengan Pmebelajaran Akidah Akhlak Di Mtsn Gresik - Nurhidayah, Evi; Shohib, Muhammad (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
Moderate Islamic education is a crucial pillar in shaping students' character to be tolerant, just, and peace-loving, especially in a pluralistic society. MTsN Metatu Gresik, as a formal educational institution, strives to integrate religious moderation values into the learning process, particularly in the subject of Aqidah Akhlak (Islamic Creed and Ethics). This study aims to explore the process of integrating Islamic moderation values in Aqidah Akhlak learning and its implications for students. Employing a qualitative approach with a case study method, data were collected through in-depth interviews, observation, and documentation. The results show that values such as tawasuth (moderation), tasamuh (tolerance), tawazun (balance), and i’tidal (justice) are integrated through curriculum planning, contextual and dialogic teaching methods, and teacher role-modeling. The implications are evident in students’ behavior, which becomes more inclusive, open to differences, and balanced in religious practice. This study indicates that Aqidah Akhlak learning holds strategic potential in instilling moderate Islamic values in a sustainable manner.